Neznani rokopisi slovenskega slovstva 17. in 18. stoletja - Ogrin, Matija (Slavistična revija, 2011)
The article gives a brief outline of three hitherto unknown 18th-century Baroque manuscripts in Slovene. Based on these and other manuscripts, the role and position of manuscripts in the literary studies of 17th- and 18th-century Slovene literature are critically reflected.
Keywords: 17./18.st.; 17th/18th cent.; manuscripts; rokopisi; Slovene literary manuscripts; Slovene literature; slovenska književnost; Slovenski rokopisi; slovensko slovstvo